POTENSI TANAMAN GANDARIA (Bouea macrophylla Griff) SEBAGAI OBAT HERBAL YANG BERAKTIVITAS ANTIOKSIDAN - DINI HANIFA; Yasmiwar Susilawati (Farmaka, 2017)
Indonesia is a country that has many medicinal plants that can be used as herbal medicine. Gandaria plant (Bouea macrophylla Griff) is one of the plants that began to be developed as  herbal medicine. Gandaria plant contains saponin and phenolic compounds. Testing of antioxidant activity on gandaria fruit juice showed IC50 value of 36.3 mg / ml, while in extract of gandaria seed showed IC50 value of 2.25 mg / ml. This review contains the chemical content of gandaria plants and their activity as antioxidants that have been studied. With this review, it is expected that people will start to cultivate this gandaria plant so that it can improve the economy and give an opportunity to the researchers to export the efficacy of this plant, especially its therapeutic potential. In addition it is expected this plant can be utilized by the herbal medicine industry into herbal medicine preparation. Keywords: Bouea macrophylla Griff, chemical content, antioxidant, herbal medicine